Microorganisms that attack forest species in the north of the state of Mato Grosso - E. P. Amorim (Scientific Electronic Archives, 2018)
Sawnwood presents one of the main forest products commercialized in the northern region of southern Amazonia, but due to its anatomical, chemical and physical composition, it becomes a target of deterioration of xylophagous organisms in general, due to the presence of parenchyma tissue in its constitution , The arrangement of the elements gives greater or less resistance to the proliferation of fungi in the cell wall, since wood that has high volumes of extractives, become more resistant and gives the wood a lower degree of susceptibility to the development of organisms in the cellular wall of the wood, works which identify xylophagous organisms in wood, are still in the initial phase, with few scientific studies on species of commercial interest. Thus, the general objective of the work is to identify the microorganisms that attack the wood of native species of southern Amazonia, as well as to classify the types of fungi attack in the woods, for the development of the study, such as the following species: cedrinho (Erisma uncinatum); white cedar (Erisma bicolor); cupiúba (Goupia glabra); Rosinha (Vochysia maxima). Six genera of fungi under the wood solution were identified during the evaluation period: Trichorderma sp; Paecilomyces variotii; Graphium arrosporium; Rhizoctonia solani; Lasioplodia theobromae and Fusarium sp. are that they are classified in relation to the damage of the wood as stains and emboloradores. Trichorderma and Paecilomyces variotii are categorized as wood shapers, due to an increase in quality, a quality of the wood, thus reducing its technological properties.